PENGARUH PENGGUNAAN FITUR PELATIHAN MANDIRI PADA PLATFORM RUANG GTK (GURU DAN TENAGA KEPENDIDIKAN) TERHADAP KOMPETENSI PEDAGOGIK GURU KELAS SEKOLAH DASAR DI KECAMATAN SABBANGPARU KABUPATEN WAJO - Ansar; Andi Makkasau; Erma Suryani Sahabuddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Ansar, 2025. "“The Influence of the Use of Independent Training Features on the Ruang GTK (Teachers and Education Personnel) Platform on the Pedagogical Competence of Elementary School Teachers in Sabbangparu District, Wajo Regency”". Educational Administration Study Program, Postgraduate Program, Makassar State University. (supervised by Dr. Andi Makkasau, M.Si.. and Dr. Erma Suryani Sahabuddin, M.Si.). This study aims to determine the effect of utilizing the Self-Training feature on the Ruang GTK Platform on the pedagogical competence of elementary school teachers in Sabbangparu District, Wajo Regency. The background of this research is rooted in the transformation of the national education system, which requires teachers to be adaptive to technological advancements and the implementation of the Merdeka Curriculum. The Ruang GTK Platform, a rebranding of the Merdeka Mengajar Platform, provides a Self-Training feature designed to enhance teacher quality and professionalism through flexible and independent learning access. This research employs a descriptive quantitative approach using questionnaires and open interviews for data collection. The sample consisted of 75 homeroom teachers from Cluster IV of Sabbangparu District. The results show that the level of utilization of the Self-Training feature is high, as is the level of teachers’ pedagogical competence. Simple linier regression analysis revealed a positive and significant influence between the use of the Self-Training feature and the teachers’ pedagogical competence. Thus, it can be concluded that the utilization of the Self- Training feature on the Ruang GTK Platform significantly contributes to improving teachers’ pedagogical competence, especially in the areas of lesson planning, student- centered instruction, and constructive assessment and feedback. This study recommends optimizing the use of the Ruang GTK Platform as a sustainable means of professional development for teachers.